The Role of Female Directors and CSR Committees on Corporate Social Responsibility Disclosure - Ludya, Angeliqa; Dewi, Sari (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 1 (2024), 2024)
This study investigates the relationship between female directors and Corporate Social Responsibility (CSR) disclosure in Indonesian listed companies on the Indonesia Stock Exchange (IDX). Utilizing a sample of 45 companies with sustainability and financial reports from 2017 to 2021, the research employs the Global Reporting Initiative (GRI) Index with 94 items to measure CSR disclosure. Findings reveal a significant negative impact of female directors on CSR when their number falls below critical mass, suggesting potential tokenism. Moreover, Female Directors with Accounting Expertise (FDAE) are found to be token figures, contributing insignificantly to CSR. The study proposes the establishment of CSR Committees as a more effective means to leverage women's involvement in CSR. The research underscores the need for regulatory frameworks to encourage gender diversity and CSR Committees within companies, emphasizing their positive impact on corporate governance, social responsibility, and sustainability reporting. Keywords: female directors, female director expertise, csr committee, csr disclosure